2009
DOI: 10.1186/1479-5868-6-30
|View full text |Cite
|
Sign up to set email alerts
|

Computer-tailored physical activity behavior change interventions targeting adults: a systematic review

Abstract: Background: Increasing physical activity is important in the promotion of better health. Computer-tailored behavior change programs have shown promise in changing lifestyle risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(130 citation statements)
references
References 35 publications
5
122
2
Order By: Relevance
“…For example, computer-tailoring could be used to include ideas for fitting physical activity into a daily schedule for a person who reports that lack of time is a major barrier to physical activity but omit this material for people who do not identify time as a major barrier to physical activity. Across the general population, computer-tailored physical activity interventions have been found to be more effective than interventions with generic content (Broekhuizen, Kroeze, Poppel, Oenema, & Brug, 2012;Lustria et al, 2013;Neville, O'Hara, & Milat, 2009), although it remains unclear whether such an intervention would be beneficial when targeting people with depressive symptoms.…”
Section: Physical Activity Intervention Features For People With Deprmentioning
confidence: 99%
“…For example, computer-tailoring could be used to include ideas for fitting physical activity into a daily schedule for a person who reports that lack of time is a major barrier to physical activity but omit this material for people who do not identify time as a major barrier to physical activity. Across the general population, computer-tailored physical activity interventions have been found to be more effective than interventions with generic content (Broekhuizen, Kroeze, Poppel, Oenema, & Brug, 2012;Lustria et al, 2013;Neville, O'Hara, & Milat, 2009), although it remains unclear whether such an intervention would be beneficial when targeting people with depressive symptoms.…”
Section: Physical Activity Intervention Features For People With Deprmentioning
confidence: 99%
“…By exploring alternative forms, such as a web-based programme, patients that potentially would decline standard PR are provided with an alternative form of intervention. Alternative formats of CR, including homebased CR such as the Heart Manual and the Angina Plan, 41 have been shown to be an effective alternative to conventional CR. In both randomisation groups, when patients were asked, the highest per cent stated their preference was the web programme.…”
Section: Non-clinical Study Outcomesmentioning
confidence: 99%
“…asthma, depression, diabetes, etc. ), the evidence suggests that tracking may be beneficial [19][20][21][22][23], however, use in the clinical setting remains limited. Research on primary care providers' perceptions of information technologies that have been developed to be used as a diary for a specific illness, is also limited, with only a handful of studies identified [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%